La pandemia que estremece al capitalismo (I) - Katz, Claudio (2020)
The coronavirus is a natural calamity powered by capitalism, which, unlike war requires protection and not destruction of human lives. It detonated previous tensions of financialization and overproduction and precipitated accumulated imbalances with globalization, urbanization, and agribusiness. The crisis erupted due to the absence of health correlates of globalization. The denialist contrast between health and economy is false. Productive activity can adapt to the emergency, through regulations that neoliberalism rejects. The pandemic's warnings were ignored because of the low cost effectiveness of its prevention, and current competition among pharmaceutical companies has led to piracy among governments. While China contains an infection that erupted due to the expansion of capitalism, the United States faces contagion in a chaotic way. He has already abandoned his disguise as a helper of the world. The national management of the pandemic breaks the European Union.